Using Contextual Constructs Model to Frame Doctoral Research Methodology - Knight, Shirlee-ann; Cross, D. (Informing Science Institute, 2012)
This paper presents a novel research model – Contextual Constructs Model (CCM) and the theory that underpins it – Contextual Constructs Theory (CCT). First developed as part of a complex project investigating user perceptions of information quality during Web-based information re-trieval, the CCM is not a single research method per se, but is a modelled research framework providing an over-arching perspective of scientific inquiry, by which a researcher is able to iden-tify multiple possible methods of study and analysis according to the identified research con-structs and their contexts. Central to CCM/CCT is that all research involves the fusion of two key elements: 1) context; and 2) cognitively-driven constructs; and that the co-dependent nature of the relationship between these two research components inform the research process and eventual outcomes. The resulting CCM is one that frames research as a contextual process of phases, in-dentifying the conceptual, philosophical, implementation, and evaluation tasks associated with a research investigation. The value of framing research within a CCM comes from its capacity to frame complex, real world phenomena since its epistemology is a blend of a critical-real world view – where reality can be both constructed and constant; within a systems-science paradigm – where constructs are not reduced to isolated parts, but investigated in terms of multiple co-constructions and the contextual relationships between them.